INTERAKSI GURU DAN ANAK DALAM KEGIATAN PERAGAAN MANASIK HAJI DI PAUD - Prasanti, Ditha (Jurnal Dakwah Tabligh, 2023)
This article is the result of research and observations on the Hajj ritual activities that PAUD children follow. In this article, the author reveals the interaction of teachers and children in Early Childhood Education Institutions (PAUD), in participating in the Hajj ritual activities held by the Ministry of Religion in Bandung. This is interesting to study because so far the writer has seen various literary studies that discuss aspects of inculcating religious and moral values, but no one has revealed the interactions that occur between teachers and children in PAUD. Therefore, the author would like to know the main reasons for participating in the Hajj ritual activities for children of Al Amanah PAUD Bandung and the interactions between teachers and children in the Hajj ritual activities. The authors used a qualitative approach with a case study method in this study. Data collection techniques are carried out through interviews, observation, and study of literature. The research results obtained are as follows; 1) Hajj rituals for PAUD children are mandatory for the main reason as a learning process to introduce the implementation of the pillars of Islam that have been taught to children; 2) interactions that occur between teacher and child can add to the closeness of interpersonal relationships, the existence of "take and give" which is a method of Islamic learning in providing knowledge about the teachings of Islam to hajj to children in PAUD.